Mechanistic and kinetic investigation on maximizing the formation of levoglucosan from cellulose during biomass pyrolysis. (15th February 2021) - Shaw, Alexander; Zhang, Xiaolei; Kabalan, Lara; Li, Jun
Highlights: Cellulose whole chain depolymerisation kinetic model was developed. Reaction temperature and residence time play key role in levoglucosan formation. Anhydro-oligosaccharides formed and consumed rapidly above 600 °C. Levoglucosan formation rate hindered at 550 °C and below. Established mechanisms cannot account for rapid experimental levoglucosan formation. Abstract: Attempts to understand and control the formation of levoglucosan, as a key bio-oil compound and an important intermediate chemical, during biomass pyrolysis have recently generated a large number of experimental and computational studies. Whilst promising mechanisms have been put forward to explain levoglucosan formation, there has yet to be clarity on the factors that inhibit the stoichiometric yields from cellulose, and, current available mechanisms adopt model compounds of short chain oligosaccharide structures rather than cellulose polymer. In this work, kinetic models describing cellulose (with Degree of Polymerisation DP of 2048) decomposition and levoglucosan formation have been constructed. It was found that temperature and residence time co-ordinately influenced the yield of levoglucosan, i.e. maximum yield can be reached within 80 s at 600 °C, however, around 10 min is required at 550 °C. Anhydro-oligosaccharides greater than DP8 will be generated and then consumed in 60 s with pyrolysis temperatures of 500 °C and over. The results also showed that the current available concerted initiation and depropagation reactions are insufficient to explain the experimentally observed high rates of cellulose depolymerisation and levoglucosan formation, other key factors such as side reactions have to be considered. Additionally, it was found that the rate of levoglucosan generation is independent of the initial cellulose chain length, which is a finding that will facilitate future studies in the area of bioenergy and biomass decomposition.